2018
DOI: 10.4103/jomfp.jomfp_129_17
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of extracellular matrix metalloproteinase inducer (EMMPRIN) in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: Background:In oral squamous cell carcinoma (OSCC), extracellular matrix metalloproteinase inducer (EMMPRIN) expression has been noted in the cell membrane throughout the epithelium of the lesion, suggesting its increased expression.Objectives:The present study was conducted to evaluate and compare the expression of EMMPRIN in the normal oral mucosa (NOM), different histological grades of oral epithelial dysplasia (OED) and OSCC.Materials and Methods:A total of 100 formalin-fixed paraffin-embedded tissue blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Higher expression was found in clinical stage III compared to stage I/II and was associated with aggressiveness of tumor bone cells [113]. A significant association between the expression of CD147 protein and oral squamous carcinoma (OSCC) stage was reported in a cohort of 100 tissue blocks [114]. Our previous studies in OSCC tumors demonstrated increased expression of CD147 compared to dysplastic lesions.…”
Section: Cd147 As a Prognostic Biomarkermentioning
confidence: 99%
“…Higher expression was found in clinical stage III compared to stage I/II and was associated with aggressiveness of tumor bone cells [113]. A significant association between the expression of CD147 protein and oral squamous carcinoma (OSCC) stage was reported in a cohort of 100 tissue blocks [114]. Our previous studies in OSCC tumors demonstrated increased expression of CD147 compared to dysplastic lesions.…”
Section: Cd147 As a Prognostic Biomarkermentioning
confidence: 99%
“…Stromal cells include fibroblasts, macrophages, and vascular endothelial cells that secrete MMPs into the extracellular space [ 28 ]. The extracellular MMP inducer (EMMPRIN) stimulates MMP synthesis in stromal fibroblasts at early stages of tumorigenesis, and EMMPRIN expression also correlates with the grade of OED patient samples [ 29 ]. MMP-9 expression and tumor vascularity progressively increase from normal mucosa to OED, indicating an additional pro-angiogenic role of MMPs in early tumor formation [ 24 ].…”
Section: Extracellular and Cell Surface Biomarkersmentioning
confidence: 99%
“…It has been reported that variations in EMMPRIN glycosylation are also associated with multidrug resistance in human leukemia ( 23 ). Furthermore, EMMPRIN is highly expressed in the malignant tumor tissues ( 24 , 25 ) involved in human gliomas ( 26 , 27 ), suggesting that it may play roles in the progression of malignant gliomas.…”
Section: Introductionmentioning
confidence: 99%